Analisis Kelayakan Investasi Penggunaan Teknologi Crude Oil System di Departemen Power Plant Pt Newmont Nusa Tenggara - Pitrandjalisari, Vitri (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
The study is to discuss application of crude oil system to process used oils generated from PTNNT’s power plant in order to optimize transportation cost from power plant to landfillarea. This study analyzes whether the system is in compliance with technology and financial aspects of plant environment. Data required to solve the problems that may occur i.e. price ofthe equipment to implement crude oil system, operational and installation costs, equipment durability, waste management data, act or government regulation concerning waste management. Based on technic aspect, PTNNT has minimize the quantity of its hazardous and toxic wastes, reduce cost to dispose hazardous and toxic wastes, minimize spill risks, and minimize risk in using main fuel; and financial aspect, by using several methodes: Pay Back Periode, Net Present Value, Profatibility Index, and Internal Rate of Return PT NNT has obtained the result which is the implementation of crude oil system in PTNNT’s power plant is feasible.